PENGARUH MENGIKUTI PROGRAM KAMPUS MENGAJAR TERHADAP MINAT MENJADI GURU PADA MAHASISWA UNJ - Shinta; Budiaman; Nandi Kurniawan (CV. ADIBA AISHA AMIRA, 2024)
The interest of students to become teachers is very worrying, as well as education students to become teachers really need attention. The importance of interest as a motivation for prospective teacher students to become professional teachers is the basis for the need to increase student interest in becoming teachers. This research aims to determine the influence of the campus teaching program on interest in becoming teachers among Jakarta State University students participating in the campus teaching program. This study uses a quantitative approach. The subjects in this research were Jakarta State University students participating in the class 5 teaching campus program. The results of the research showed that there was a positive influence of the teaching campus program on interest in becoming teachers among Jakarta State University students as indicated by a positive regression coefficient of 0.479. This means that every time there is an addition of one unit of the campus teaching program variable, the value of the variable interest in becoming a teacher increases by 0.479. This interest is supported by campus teaching programs, feelings about teaching, attention to the quality of education, ideals, and perceptions of the teacher's profession & welfare. Meanwhile, what hinders students from becoming teachers is mostly influenced by the perception of the teacher's profession and welfare as well as social friends. Based on the results of the research and discussion, it can be concluded that the campus teaching program has a positive effect on the interest in becoming teachers at Jakarta State University students.